Changing Definitions of Climate in Polish and English Dictionaries - Kwaśniewska, Marta (Respectus Philologicus, 2020)
The present article sets out to examine the dictionary definition entries concerning the concept of climate. Both Polish and English dictionaries are included, as well as historical and contemporary entries. The data is composed of thirteen dictionary entries, published in the last two hundred years. The material is examined qualitatively. The results are presented in the form of a table, where one may find all the aspects of meanings identified in the definitions. A supplement data extracted from the English historical corpus is also provided. The results have revealed that semantic change did occur in both the Polish and the English language. However, the change is more visible in the Polish dictionaries. The subsidiary differences could influence the way the word is employed in certain contexts and thus, differentiate the employment of the same concept in the two languages. Nevertheless, the contemporary definitions are almost identical in both languages, in contrast to the historical ones.
Keywords: climate; dictionary definition; semantic change